(untitled) (Veterinary Science, 2017)
One of the ways to ensure safety in a food industry is the incorporation of hygiene and sanitation. Among the systems of quality management in the food industry are SSOP (Sanitation Standard Operating Procedures) called. Production of flour, although it is a food low microbial risk, also requires hygienic practices to ensure the safety of the same. For processing health and hygiene conditions of accommodation requirements and quality of raw materials and staff training are required; to implement a POES. The aim of this work is to develop a manual of POES in Milling Industry to ensure sanitary conditions (hygiene, cleaning and disinfection) in order to produce a safe food product. Different stages of value addition of wheat that coordinates toured the mill. After collecting all the information and considering the global knowledge production and storage comodity, an interdisciplinary team to awareness and drafting the final manual was formed. This was divided into the following areas: • Gathering Wheat • Storage of toxic products (disinfectants, insecticides, etc.) • Storage of empty containers (bags of flour) • Deposit Commodities• Personal Hygiene • Administrative and Production Sector The application of the POES in the flour mill optimized resources and processes, reduced costs, maximized profits and managed security and efficiency in the organization obtaining harmless flour reducing the level of nonconforming product.